Length and Thickness of Vertebral Artery Groove of Dry Ossified Human Atlas Vertebra - Rahman, Sadia; Ara, Shamim; Sayeed, Sharmina; Banu, Masuma Akhtar; Kashem, Kanetarin (Bangladesh Journal of Anatomy, 2015)
Context: The superior surface of the posterior arch of the atlas vertebra behind its lateral mass has a vertebral artery groove. The contents of this groove are third part of vertebral artery, venous plexus and first cervical nerve. Morphometric data of vertebral artery groove is helpful for the spine surgeons to avoid iatrogenic injury of these vital structures during posterior approach. Materials and Methods: A cross-sectional, analytical type of study was conducted in the Department of Anatomy, Dhaka Medical College, Dhaka from January 2012 to July 2013. Inner and outer groove length and thickness of the vertebral artery groove was measured with the help of flexible metallic wire and digital slide calipers. Results: There was no significant difference (P>0.10) in the mean length of inner border between right and left groove for vertebral artery. But outer border of left groove for vertebral artery was larger than right groove for vertebral artery (P<0.001). The mean thickness of the groove for the right and left vertebral artery was not significantly different (P>0.50). Bangladesh J. Anat. 2015; 13(1) : 8-10